HRM practices for knowledge management and retail firms’ performances: a comparative study among Malay and Chinese firms - Tehseen, Shehnaz *; Khalid, Saddam; Rather, R. A.; Qureshi, Zuhaib Hassan; Halbusi, Hussam Al (Allied Business Academies, 2020)
The current study examines the impact of human resource management (HRM) practices for knowledge management (KM) on perceived business performances among Malay and Chinese firms in Malaysia. Data were collected through a face-to-face survey with 200 owners of firms, comprising 100 Malay entrepreneurs and 100 Chinese entrepreneurs, operating in the retail sector of Klang Valley, Malaysia. Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA). The results of PLSSEM revealed that HRM practices for KM have a direct and positive impact on the perceived financial performance, perceived non-financial performance, and perceived business growth of Malay and Chinese firms. However, non-significant impact of HRM practices for KM on perceived performance relative to competitors was found among Chinese firms. Results of MGA revealed significant differences between Malay and Chinese firms in relation to the impact of HRM practices for KM on perceived financial performance and perceived performance relative to competitors.